MEMBANGUN BAHASA KOMUNIKATIF UNTUK ANAK USIA DINI - Rina Devianty (NIZHAMIYAH, 2019)
Language is the most effective communication tool in social interaction. When communicating, communicative language skills are certainly needed by anyone, including children and parents. Parents have a very important role to play in improving communicative language mastery for early childhood. By using communicative language, it is expected to have a positive impact on children's language development. So, children are not only passive language users, but also become active language users.